Hierarchical control system for a flexible microgrid with dynamic boundary: design, implementation and testing. Issue 4 (30th September 2019) - Yin, He; Ma, Yiwei; Zhu, Lin; Hu, Xiaotong; Su, Yu; Glass, Jim; Wang, Fred; Liu, Yilu; Tolbert, Leon M.
Abstract : The design, implementation, and testing of a control system for a flexible microgrid (MG) is presented in this study. The MG controllers can be implemented in a real‐world MG with multiple smart switches, photovoltaic panel system, and battery energy storage systems (BESSs). With the benefits from smart switches, the MG has unique characteristics such as dynamic boundary and flexible point of interconnection (POI) concepts. To control such a unique MG and realise the dynamic boundary, an MG central controller and two types of local controllers are implemented. Compared to the MG with fixed boundary, the MG with dynamic boundary can have smaller BESS capacity, better utilisation of renewable energy, and multiple POI options. Also, compared with IEEE Std 2030.7–2017, the topology identification and active and reactive power balance functions are newly designed to realise the dynamic boundary concept. The planned islanding and reconnection functions are modified to realise the flexible POI concept. These functions are introduced including the software architecture, cooperation, and interaction among them. Finally, a hardware‐in‐the‐loop testing platform based on the Opal‐RT real‐time simulator is set up to verify the performance, realisation of the dynamic boundary, and flexible POI concepts with four comprehensive test scenarios.